2015
DOI: 10.3168/jds.2015-9721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ruminal dosing of Holstein cows with Megasphaera elsdenii on milk fat production, ruminal chemistry, and bacterial strain persistence

Abstract: Megasphaera elsdenii is a lactate-utilizing bacterium whose ruminal abundance has been shown to be greatly elevated during milk fat depression (MFD). To further examine this association, a total of 23 cannulated multiparous Holstein cows were examined in 3 experiments in which strains of M. elsdenii were directly dosed into the rumen (~2 × 10(12) cells/dose); control cows were dosed with sterile lactate-free culture medium. Cows were fed a total mixed ration (292 g of starch/kg of dry matter) that contained pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
1
23
0
3
Order By: Relevance
“…Interestingly, previous studies attempted to enrich the rumen of cows with M. elsdenii isolated from the rumen, in order to stabilize ruminal pH by decreasing lactate concentration and alter VFA profile toward increasing acetate and butyrate production (Zebeli et al, 2012;Weimer et al, 2015). Despite being unsuccessful in stably transplanting the bacteria and altering rumen composition, focusing on this species or other lactate utilizers may represent an interesting avenue worth pursuing for the purpose of both increased feed efficiency and methane mitigation.…”
Section: Methane Emissionmentioning
confidence: 99%
“…Interestingly, previous studies attempted to enrich the rumen of cows with M. elsdenii isolated from the rumen, in order to stabilize ruminal pH by decreasing lactate concentration and alter VFA profile toward increasing acetate and butyrate production (Zebeli et al, 2012;Weimer et al, 2015). Despite being unsuccessful in stably transplanting the bacteria and altering rumen composition, focusing on this species or other lactate utilizers may represent an interesting avenue worth pursuing for the purpose of both increased feed efficiency and methane mitigation.…”
Section: Methane Emissionmentioning
confidence: 99%
“…Because M. elsdenii has been shown to produce trans ‐10, cis ‐12 ‐ CLA in pure cultures, Weimer et al . () tested the effects of ruminal dosing of several strains of M. elsdenii but could not trigger a milk fat depression because the dosed strains did not establish itself in the rumen. Maia et al .…”
Section: Rumen Bh: a Microbiota Response To Dietary Ufasmentioning
confidence: 99%
“…More specifically, Rico et al (2015) showed that the Butyrivibrio group decreases and M. elsdenii increases during induction of milk fat depression, with reverse changes observed during recovery. Because M. elsdenii has been shown to produce trans-10,cis-12-CLA in pure cultures, Weimer et al (2015) tested the effects of ruminal dosing of several strains of M. elsdenii but could not trigger a milk fat depression because the dosed strains did not establish itself in the rumen. Maia et al (2007) reported that the high abundance of this species with high starch and high oil diets probably links to its resistance to both low pH and UFA, but Palmonari et al (2010) observed that the link between milk fat depression and M. elsdenii abundance is independent on rumen pH.…”
Section: Biohydrogenating Micro-organisms and Enzymesmentioning
confidence: 99%
“…Marx et al (2011), for example: Megasphaera elsdenii is a lactate-utilizing bacterium whose ruminal abundance has been shown to be greatly elevated during milk fat depression. Second Weimer et al (2015) studied the effects of the addition of M. elsdenii and concluded milk yield and composition were not affected by dosing. Ruminal pH, VFA and lactate did not differ between dosed and control cows, although acetate-to-propionate ratio declined in both groups and butyrate increased after dosing with M. elsdenii.…”
Section: Bacteriamentioning
confidence: 99%